Epigenetic Shifts in Preterm Neonatal Microbiome - Agnieszka Buliszak; Piotr Marcjasz; Anna Bioły; Monika Babczyńska; Agnieszka Borończyk; Piotr Zając (Quality in Sport)
Introduction and Study Aim: Preterm birth (<37 weeks) causes ~15 million births yearly and is a major contributor to neonatal morbidity and mortality [1]. These infants face developmental challenges, including disrupted microbial colonization and immature regulatory systems. Epigenetic modifications—heritable changes in gene expression without DNA sequence alteration—mediate environmental influences during this critical period [2]. This paper explores how the preterm microbiome and epigenetic mechanisms interact and influence health outcomes. Brief Description of Current Knowledge: The preterm gut microbiome shows reduced diversity and more hospital-acquired bacteria [3]. Cesarean delivery, antibiotics, and lack of maternal microbes contribute to this dysbiosis. Beneficial colonizers (e.g., bifidobacteria) are reduced, while pathogens (e.g., Staphylococcus, Enterobacteriaceae) increase, linked to NEC and sepsis. Epigenetic shifts also occur rapidly in response to inflammation and stress [3]. Microbial metabolites (e.g., butyrate, folate) can alter epigenetic programming [5], and prenatal epigenetic states may shape microbial colonization [2]. Summary/Conclusions: Microbiome-epigenome interactions may shape immunity and development beyond infancy. Disruptions may imprint harmful epigenetic changes. More research is needed to clarify mechanisms and guide interventions like probiotics or epigenetic therapies.